Social suffering, HIV, and narratives surrounding death among trans women in Lima - Núnez-Curto Sifuentes, Arón (2019)
Based on the ethnographic study of the course of the disease, care and death of four trans women and transvestites in the city of Lima. This paper analyzes the narratives about HIV/AIDS, health care, and ways to cope with adversity and death, as part of the explanations and assessments of the trans women and transvestites who took care of the deceased. On the one hand, we analyze the impact of institutional violence and social inequities on the limited possibilities that the deceased and their care networks had to deal with the disease processes caused by HIV infection without access to treatment and care. In addition, we discuss that the effects of a neoliberal perspective on health care and a rhetoric of HIV/AIDS around the perspective of epidemiological risk are discourses articulated in the narratives analyzed. Both discourses emphasize individual responsibility as the way to face adversity and health problems. Finally, the narrative of “messy life” is especially significant, because it allow us to analyze the dynamics around the effects of HIV/AIDS as a control device, and the stigma against transgender people as a form of producing suffering and vulnerability among trans women and transvestites.